Influence of Femininity and Masculinity Traits on Participation and Performance in Science, Technology, Engineering and Mathematics of Undergraduate Students in Tanzania - Rukondo, Nyanjiga; Kinyota, Mjege (Papers in Education and Development, 2022)
This study investigated whether women and men differed in terms of their femininity, masculinity, gender negatives stereotypes, persistence, self-efficacy and performance in Science, Technology, Engineering and Mathematics (STEM), and established the relationship among these variables. A sample of 721 undergraduate students majoring in STEM in a teacher education program was used. The study was conducted in one public university in Tanzania. The study reveals that there is a significant difference in two aspects only. Specifically, male students held gender negative stereotypes regarding females ' abilities in STEM. They were also significantly self-officious as compared to female students. Surprisingly, it was revealed that females outperformed males in several masculinity traits. In addition, there was a significant correlation among variables, with notable differences across gender. Keywords: femininity, gender, masculinity, self-efficacy, STEM, Tanzania